Glucosamine Ameliorates Symptoms of High-Fat Diet-Fed Mice by Reversing Imbalanced Gut Microbiota - Yuan, Xubing; Zheng, Junping; Ren, Lishi; Jiao, Siming; Feng, Cui; Du, Yuguang; Liu, Hongtao (Frontiers in Pharmacology, 2021)
Glucosamine (GlcN) is used as a supplement for arthritis and joint pain and has been proved to have effects on inflammation, cancer, and cardiovascular diseases. However, there are limited studies on the regulatory mechanism of GlcN against glucose and lipid metabolism disorder. In this study, we treated high-fat diet (HFD)-induced diabetic mice with GlcN (1 mg/ml, in drinking water) for five months. The results show that GlcN significantly reduced the fasting blood glucose of HFD-fed mice and improved glucose tolerance. The feces of intestinal contents in mice were analyzed using 16s rDNA sequencing. It was indicated that GlcN reversed the imbalanced gut microbiota in HFD-fed mice. Based on the PICRUSt assay, the signaling pathways of glucolipid metabolism and biosynthesis were changed in mice with HFD feeding. By quantitative real-time PCR (qPCR) and hematoxylin and eosin (H&E) staining, it was demonstrated that GlcN not only inhibited the inflammatory responses of colon and white adipose tissues, but also improved the intestinal barrier damage of HFD-fed mice. Finally, the correlation analysis suggests the most significantly changed intestinal bacteria were positively or negatively related to the occurrence of inflammation in the colon and fat tissues of HFD-fed mice. In summary, our studies provide a theoretical basis for the potential application of GlcN to glucolipid metabolism disorder through the regulation of gut microbiota.